Antigingivitis efficacy of a sodium bicarbonate toothpaste: Pooled analysis. Issue 1 (5th October 2022) - Parkinson, Charles R.; Butler, Andrew; Ling, Martin R.
Abstract: Objective: The objective of this study was to investigate the antigingivitis and antiplaque treatment effect of a toothpaste containing 67% w/w sodium bicarbonate, at the individual tooth site, tooth region and whole mouth (overall) level, by way of a pooled analysis of data from similarly designed clinical trials. Methods: Six randomized controlled GSKCH clinical trials, 12–24 weeks in duration, were selected based on pre‐specified criteria which included access to patient level data, pre‐treatment dental prophylaxis, >20 bleeding sites and mild–moderate gingivitis at screening and use of 67% sodium bicarbonate toothpaste and non‐sodium bicarbonate (regular) toothpaste (negative control) for ≥4 weeks. Efficacy outcomes comprised plaque index (TPI), modified gingival index (MGI) and gingival bleeding (bleeding index (BI), number of bleeding sites (BS)). Treatment comparisons were made using ANCOVA for whole mouth (overall) scores and by tooth site region (facial overall, lingual overall; margin/body overall, facial margin/body, lingual margin/body; papillae/interproximal overall, facial papillae/interproximal, lingual papillae/interproximal). Pooled data for BI, MGI, and TPI at individual tooth sites was plotted as a mouthmap to summarize treatment response (change from baseline) by tooth site, at the 24‐week timepoint. Results: For all measures, whole mouth and for all tooth regions at all post‐treatment timepoints, significant ( p < 0.001) differences in favour of the 67% sodium bicarbonate toothpaste compared with control were observed. At the 24‐week timepoint, facial regions demonstrated greater improvements than lingual regions, with the greatest between treatment improvement seen for the facial‐papillae regions for bleeding (BS/BI), facial‐margin regions for MGI and facial‐body regions for TPI. All individual tooth sites demonstrated numerically greater reductions from baseline for the 67% sodium bicarbonate toothpaste than the control toothpaste following 24 weeks use, with the greatest improvements (change from baseline) seen for posterior and papillae tooth sites for bleeding, margin tooth sites for MGI and body tooth sites for TPI. Conclusion: This pooled analysis of patient level‐data, limited to GSKCH long‐term gingivitis clinical studies, demonstrates that twice daily use of a 67% sodium bicarbonate toothpaste effectively removes plaque from all tooth sites, and results in clinically significant improvements in measures of gingival health, overall and for all the tooth regions investigated, compared with a non‐sodium bicarbonate (regular) toothpaste following 24 weeks twice daily use.